2015
DOI: 10.1038/nsmb.3102
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 binds to G quadruplexes and suppresses replication over long distances

Abstract: Rif1 regulates replication timing and repair of double-strand DNA breaks. Using a chromatin immunoprecipitation-sequencing method, we identified 35 high-affinity Rif1-binding sites in fission yeast chromosomes. Binding sites tended to be located near dormant origins and to contain at least two copies of a conserved motif, CNWWGTGGGGG. Base substitution within these motifs resulted in complete loss of Rif1 binding and in activation of late-firing or dormant origins located up to 50 kb away. We show that Rif1-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
171
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(176 citation statements)
references
References 46 publications
4
171
1
Order By: Relevance
“…with multiple G4 DNA ~ Our previous studies suggested a possibility that Rif1 participates in physical interactions of distant chromatin segments, contributing to the formation of chromatin loops (6)(7)9). As shown in the previous section of this report, purified muRif1 behaves as oligomers and bears at least two G4-binding domains (NTD and CTD).…”
Section: Simultaneous Interaction Of Murif1mentioning
confidence: 89%
See 2 more Smart Citations
“…with multiple G4 DNA ~ Our previous studies suggested a possibility that Rif1 participates in physical interactions of distant chromatin segments, contributing to the formation of chromatin loops (6)(7)9). As shown in the previous section of this report, purified muRif1 behaves as oligomers and bears at least two G4-binding domains (NTD and CTD).…”
Section: Simultaneous Interaction Of Murif1mentioning
confidence: 89%
“…8B, column 4), but unaffected by addition of even 10-fold excess of T 6 [GA] 12 DNA (Fig. 8B, column 5).…”
Section: Simultaneous Interaction Of Murif1mentioning
confidence: 99%
See 1 more Smart Citation
“…Late firing of Taz1-affected origins requires telomere-associated Rif1, which also has been implicated in DNA repair (37,38). However, Rif1 binds only a subset of Taz1-associated late origins (11,38,39), and it is conceivable that Shelterin-mediated telomeric association of these origins allows Rif1 acquisition to promote proper replication and DNA repair. In other words, Taz1-bound late origins in telomeric and arm regions might be controlled in a shared nuclear compartment.…”
Section: Discussionmentioning
confidence: 99%
“…One microgram of the sheared DNA was denatured at 100°C for 10 min, and BrdUsubstituted DNA was immunoprecipitated by Dynabeads sheep-anti mouse IgG (11031; Thermo Fisher) attached to anti-BrdU antibody (MBL, MI-11-3, 2.5 μg). The beads were washed with lysis buffer and DNA was eluted, as described (50,51). The immunoprecipitated DNA was treated with proteinase K, purified by a QIAquick PCR purification kit (Qiagen), and used for quantitative PCR performed with SYBR Premix Ex Taq (TaKaRa Bio) on a LightCycler 480 (Roche).…”
Section: Methodsmentioning
confidence: 99%